A Review of Candida auris: Environmental Persistence and Evidence-Based Decontamination and Prevention Strategies - Krzyzaniak, Marta; Brynczka, Izabela; Patrzykąt, Klaudia Martyna; Gorzoch- Burduk, Zofia; Puzio, Julia; Marcinkowska, Paula; Jezierski, Michał; Popielarska, Kinga; Nowicka, Ewelina; Wróblewska, Kamila (Quality in Sport, 2026)
Background. Candida auris is an emerging, multidrug-resistant fungal pathogen of significant public health concern. Noted for its environmental persistence and high transmissibility, it poses a substantial threat in healthcare settings, particularly in intensive care units, driving the need for specific infection control protocols. Aim. The aim of this study was a comparative analysis of environmental disinfection methods used in the prevention and control of Candida auris in various countries and healthcare facilities. Material and methods. This review analyzed literature from 2016-2025, sourced from databases such as PubMed, alongside public health guidelines and epidemiological reports. A comparative analysis of the selected data was conducted. Results. Disinfection strategies against C. auris primarily recommend chlorine- and hydrogen peroxide-based agents, with UV-C and vaporized hydrogen peroxide (VHP) noted as supplementary measures. A comparative analysis revealed significant international divergence, particularly regarding quaternary ammonium compounds (QACs), which are largely restricted except in specific contexts like India. Overall efficacy is highly variable and dependent on disinfectant selection, workflow, staff training, and the consistency of protocol implementation. Conclusions. Chlorine- and peroxide-based disinfectants are most effective against C. auris, while QACs are discouraged despite their localized use. To counter variability in international guidelines, a unified regulatory framework is recommended. Key recommendations include standardizing procedures, enhancing staff training, and maintaining strict surveillance. Further research, including hospital case studies, is needed due to insufficient current data.